Computational hemorheology of blood flow with TiO₂ nanoparticles over a non-linearly stretching sheet under magnetohydrodynamics - Zainal, Nurul Amira; Zuberi, Haris Alam; Lal, Madan (Pushpa Publishing House, 2024)
This study presents a computational analysis of the hemorheology of blood flow containing TiO2 nanoparticles over a non-linearly stretching sheet under the influence of magnetohydrodynamics (MHD). The Sisko blood flow model is employed to capture the non-Newtonian characteristics of the blood. The governing equations are derived and transformed into a set of non-linear ordinary differential equations (ODEs) using appropriate similarity variables. These equations are then solved numerically using the 4th-5th order Runge-Kutta-Fehlberg (RKF45) method. The results demonstrated that an increase in Sisko material parameter enhances the velocity of nanofluid. Increase in non-linear stretching parameter leads to a thinner boundary layer, thereby enhancing heat transfer at the surface. The findings underscore the potential of TiO2 nanoparticles in significantly improving heat transfer efficiency in biomedical and industrial applications.